2021
DOI: 10.3390/nu13072182
|View full text |Cite
|
Sign up to set email alerts
|

AB-Kefir Reduced Body Weight and Ameliorated Inflammation in Adipose Tissue of Obese Mice Fed a High-Fat Diet, but Not a High-Sucrose Diet

Abstract: Consumption of different types of high-calorie foods leads to the development of various metabolic disorders. However, the effects of multi-strain probiotics on different types of diet-induced obesity and intestinal dysbiosis remain unclear. In this study, mice were fed a control diet, high-fat diet (HFD; 60% kcal fat and 20% kcal carbohydrate), or western diet (WD; 40% kcal fat and 43% kcal carbohydrate) and administered with multi-strain AB-Kefir containing six strains of lactic acid bacteria and a Bifidobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…High fat diets has been reported to increase weight gain, affect immune organ weight and indices ( Jin et al, 2017 ; Li et al, 2020 ; Yoshizaki et al, 2020 ). Probiotics reduce excessive weight increase in animals fed high fat diet ( Kong et al, 2019 ; Chen Y. T. et al, 2021 ). From the results of the in vivo experiments, we observed that, Bacillus toyonensis SAU-19 and SAU-20 could reduce weight gain in mice compared to the HF group.…”
Section: Discussionmentioning
confidence: 99%
“…High fat diets has been reported to increase weight gain, affect immune organ weight and indices ( Jin et al, 2017 ; Li et al, 2020 ; Yoshizaki et al, 2020 ). Probiotics reduce excessive weight increase in animals fed high fat diet ( Kong et al, 2019 ; Chen Y. T. et al, 2021 ). From the results of the in vivo experiments, we observed that, Bacillus toyonensis SAU-19 and SAU-20 could reduce weight gain in mice compared to the HF group.…”
Section: Discussionmentioning
confidence: 99%
“…However, fatty streaking of the aorta was not different between groups [59]. Kefir containing several strains of lactobacilli reduced body weight gain, insulin resistance, and hepatic steatosis in mice fed a high-fat diet [60]. Complementary results were seen in an experiment in which three different isolates (Lactobacillus acidophilus LA15.…”
Section: Metabolic Effectsmentioning
confidence: 70%
“…In total, 12 genera correlated significantly with at least one obesity parameter (Figure 4K). The relative abundances of Roseburia, [ 33 ] Anaerovorax, Ruminiclostridium, [ 34 ] Tyzzerella, [ 35 ] and Lachnospiraceae_NK4A136_group correlated positively with the levels of serum transaminases, LPS, and liver weight and negatively with TJ gene expression levels. However, the relative abundances of Parasutterella and Akkermansia [ 36 ] correlated positively with TJ gene expression.…”
Section: Resultsmentioning
confidence: 99%